Tata Kelola Penerapan Program Bantuan Langsung Tunai (BLT) Di Kota Tangerang - Liani Febrianti; Nanan Sujana; Pri Utami (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Governance of the Implementation of the Direct Cash Assistance Program (BLT) in Periuk District, Tangerang City. This study aims to find out how the governance of the implementation of the Direct Cash Assistance Program (BLT) in Periuk District, Tangerang City and to find out what factors are inhibiting the governance of implementing the Direct Cash Assistance Program (BLT) in Periuk District. This study uses a descriptive qualitative approach. Data were collected by observation, interview and documentation techniques. The types and sources of data are primary data and secondary data. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The theoretical concept used in this study is the Good Governance Indicator in Mahsun et al (2018: 48), namely Transparency, Accountability, Participation.The results of the research and changes that have been carried out by researchers, as well as based on research indicators which are the source of the basis for this study include transparency, accountability, participation. The research results show that 2 indicators show that governance is optimal this program properly, namely the indicators of transparency (transparency), participation (participation). While the indicators of accountability still need to be improved even better. The inhibiting factors included, among other things, data from the Community Welfare Integrated Data (DTKS) that were not quite right on target and double data ownership on the identification number (NIK) or E-KTP.